Identification of active loci of a human endogenous retrovirus in neurons of patients with amyotrophic lateral sclerosis - Douville, Renée; Liu, Jiankai; Rothstein, Jeffrey; Nath, Avindra (Annals of neurology, 2011)
Objective Amyotrophic lateral sclerosis (ALS) is characterized by the progressive loss of motor neurons, of unknown etiology. Previous studies showed reverse transcriptase in serum of ALS patients at levels comparable to human immunodeficiency virus‐infected patients; however, the source and significance of the retroviral elements is uncertain. Methods Expression of a human endogenous retrovirus (HERV‐K) was determined in autopsy brain tissue of patients with ALS and compared to control populations by real‐time polymerase chain reaction followed by sequencing of the amplified genes and confirmed by immunostaining. Results HERV‐K pol transcripts were increased in patients with ALS compared to those with chronic systemic illness, but could not be detected in Parkinson disease or in the accidental death controls. Sequencing revealed several actively transcribed loci in the HML‐2 and 3 subfamilies of HERV‐K, with a specific pattern of expression including intact open reading frames and the transcription of a unique locus in ALS. The frequency of intact pol transcripts was highest in the motor cortex, and the reverse transcriptase protein was localized to cortical neurons of ALS patients. HERV‐K expression strongly correlated with TDP‐43, a multifunctional protein known to be dysregulated in ALS. Interpretation We have identified a specific pattern of HERV‐K expression in ALS, which may potentially define the pathophysiology of ALS. Targeting of activated genome‐encoded retroviral elements may open new prospects for the treatment of ALS. Ann Neurol 2011;69:141–151.